Innovative and energy-efficient insulation technology for the production of electric drives - Hofmann, Benjamin; Spreng, Simon; Franke, Jörg; Maryniak, Bernd (2014 4th International Electric Drives Production Conference, EDPC 2014 - Proceedings, 2014)
Resin applications have always been found within the production of electric drives. Replacing natural materials like tar and rubber, industrial produced polymers quickly spread amongst all major components and manufacturing steps of electric machines. Today, thermosetting resins are mainly used within the disciplines of insulation and fixation of materials, manifesting in wire enamels, impregnation varnishes, potting resins and thermally curing adhesives. As broad as their manifestations are the challenges around these products. Thermal curing generally uses an excessive amount of energy when being conducted by oven heating or infrared radiation. Alternative and particularly energy-efficient technologies are available, but have yet to be investigated from a scientific perspective. Within the research project ESolation, the FAPS institute has aimed to investigate inductive heating technology as an energy-saving method for thermosetting resin and powder coat curing to create insulating layers within an automated and flexible production of electric drives. Saving potential in the context of electrical sheet laminations has shown to be as high as up to 95% of electrical energy. In order to determine the value of this technology, simulative as well as empiric investigations have to be made to create a better understanding of how inductive heating of sheet lamination works and to determine feasibility and integration into current production processes.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Impregnation; Insulation; Resin